Programmed Cell Death Pathways in the Pathogenesis of Systemic Lupus Erythematosus - Fangyuan Yang; Yi He; Zeqing Zhai; Erwei Sun (Journal of Immunology Research)
Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease characterized by excessive inflammatory and immune responses and tissue damage. Increasing evidence has demonstrated the important role of programmed cell death in SLE pathogenesis. When apoptosis encounters with defective clearance, accumulated apoptotic cells lead to secondary necrosis. Different forms of lytic cell death, including secondary necrosis after apoptosis, NETosis, necroptosis, and pyroptosis, contribute to the release of damage-associated molecular patterns (DAMPs) and autoantigens, resulting in triggering immunity and tissue damage in SLE. However, the role of autophagy in SLE pathogenesis is in dispute. This review briefly discusses different forms of programmed cell death pathways and lay particular emphasis on inflammatory cell death pathways such as NETosis, pyroptosis, and necroptosis and their roles in the inflammatory and immune responses in SLE.